Design of Two-Wheeled Motorcycle Tire Crown Contour Bioinspired by Cat Paw Pads - Congzhen Liu; Guolin Wang; Haichao Zhou; Ye Mei; Yongqiang Li; Yalong Li; Lingxin Zhang (Applied Bionics and Biomechanics)
The grip force of tires is crucial for vehicle security and drivability under different driving conditions. A small contact area and stress concentration in the contact patch of two-wheeled motorcycle (TWM) tires result in a reduction in grip performance and wear resistance. Even worse, improving the grip and wear resistance together is difficult to achieve. The purpose of the current study is to analyze the dynamic grounding characteristics and geometry of a cat paw pad and then apply its structure to the TWM tire to improve the contact area and wear resistance under different operating conditions. A nonlinear finite element tire model that could accurately reconstruct the tire structure and realistically reflect the mechanical response to different loads was employed. Then, the accuracy of the tire model was validated by a static test with a control tire. For cats, the dynamic grounding characteristics and topology of paw pads were determined using a pressure-sensitive walkway and a three-dimensional (3D) laser scanner. The results indicated that the cat forepaw third pad (CFTP) exhibited excellent grip capacity. According to similarity transformation, a bionic tire crown was designed according to the lateral fitting curve of the CFTP. Comparative results showed the enlargement of the contact area and decreases in peak pressure and frictional energy rate for the bionic tire under different conditions. With these improvements, the grip performance was improved, and the service life was extended synchronously. These research results can be applied for the design of TWM tires, especially cross-country motorcycle tires.